2012
DOI: 10.1186/1471-2350-13-70
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the genes coding for iron binding and transporting proteins are associated with disability, severity, and early progression in multiple sclerosis

Abstract: BackgroundIron involvement/imbalance is strongly suspected in multiple sclerosis (MS) etiopathogenesis, but its role is quite debated. Iron deposits encircle the veins in brain MS lesions, increasing local metal concentrations in brain parenchyma as documented by magnetic resonance imaging and histochemical studies. Conversely, systemic iron overload is not always observed. We explored the role of common single nucleotide polymorphisms (SNPs) in the main iron homeostasis genes in MS patients.MethodsBy the pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 57 publications
0
35
0
1
Order By: Relevance
“…Rubio et al ( Rubio et al, 2004 ) reported an increased frequency of the HFE C282Y mutation in MS compared to HC (10.2% vs. 6.7%). A more recent study investigating the association of iron related polymorphisms in MS found an increased Multiple Sclerosis Severity Score (MSSS) and disease progression in H63D-, but not among C282Y- carriers ( Gemmati et al, 2012 ). Presence of any iron risk polymorphism under investigation (H63D, C282Y, and others vs. wild-type) was associated with higher EDSS, MSSS, and progression scores.…”
Section: Discussionmentioning
confidence: 99%
“…Rubio et al ( Rubio et al, 2004 ) reported an increased frequency of the HFE C282Y mutation in MS compared to HC (10.2% vs. 6.7%). A more recent study investigating the association of iron related polymorphisms in MS found an increased Multiple Sclerosis Severity Score (MSSS) and disease progression in H63D-, but not among C282Y- carriers ( Gemmati et al, 2012 ). Presence of any iron risk polymorphism under investigation (H63D, C282Y, and others vs. wild-type) was associated with higher EDSS, MSSS, and progression scores.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in genes encoding iron-binding and iron-transporting proteins are associated with disability, disease severity and early progression in MS 26 . Rithidech et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several groups reported on the genetic polymorphism of the proteins involved in iron homeostasis, but not related to iron deficiency or overload [116,117,118]. Genetic analysis of iron deficiency in mice has been evaluated [119].…”
Section: Genetic Polymorphism Of Proteins Involved In Iron Metabolismmentioning
confidence: 99%